Comparison of zinc-probiotic combination therapy to zinc therapy alone in reducing the severity of acute diarrhea - Muhammad Hatta; Supriatmo Supriatmo; Muhammad Ali; Atan Baas Sinuhaji; Berlian Hasibuan; Fera Luna Nasution (Paediatrica Indonesiana, 2011)
Background Although the incidence of diarrhea in Indonesia has declined in the last five years, the mortality rate in children under five years old is still high. Therefore, appropriate and comprehensive management of diarrhea is essential. There have been many studies on the role of zinc therapy and probiotic therapy in reducing the severity of acute diarrhea, but not many studies have compared the use of a combination of the two therapies tozinc therapy alone.Objective To compare the efficacy of zinc-probiotic combination therapy to zinc alone in reducing the severity of acute diarrhea.Methods We conducted a randomized, open-label, controlled trial from July 2009 to January 2010 in Adam Malik Hospital and Pirngadi Hospital, Medan. Children aged between 1 month and 5 years who met the criteria were divided into two groups. Group I received zinc sulphate (aged <6 months: 10 mg/day; aged 2:6 months: 20 mg/day) combined with heat-killed Lactobacillus acidophilus (3x101O CFU/day) for 10 days. Group II received only zinc sulphate at the same dosage as group I. Measurement of disease severity was based on the frequency of diarrhea (times/day) and the duration of diarrhea (hours) after initial drug consumption.Results Eighty subjects were enrolled, randomised, and divided equally into two groups. 40 children received zinc-probiotic in combination (group I) and the remainder (group II) received zinc alone. We observed significant differences in frequency of diarrhea (2.1 vs 3.1 times/day, P=0.001, 95%CI -1.62 to -0.49), and duration of diarrhea (52.1 vs. 72.6 hours, P=0.00l, 95%CI -30.91 to -10.18) in the two groups.Conclusion Combination of zinc-probiotic therapy was more effective in reducing the severity of acute diarrhea than zinc therapy alone in children under five years of age.